Albanian Cultural Representation In The City Of Venice Through Albanian Painters In Italy - Irena Ndreu (Association of Social and Educational Innovation, 2017)
Many men of education run away to European cities after the invasion of the entire Balkan Peninsula. The ideals of humanism and renaissance were affirmed, thanks to their intelligence, which brought the Greek-Roman classicism to the top of the fields of literature and art. This paper will present the works of brothers Gjon (Giovanni) and Pal (Paolo) Gazulli, the poet Michele Marulli, the writer Marin Barleti (Marino Barlezio), the philosopher Leonik Tomeu, the painter Vittore Carpaccio, excelled with their talent and works in the city of Venice. The Albanian community needed a fortune to compete with groups from other nations, with the Dalmatians among many. They needed to decorate the premises of their association with precious objects and paintings: there is proof of this in the paintings of Vittore Carpaccio, in the first years of the XVIth century. Carpaccio‟s works are important, they present, in the cycle "Stories of St. Ursula", the uniform of Albanian soldiers serving the Republic of Venice.